Molecular detection of tick-borne protozoan parasites in sika deer (Cervus nippon) from western regions of Japan - Masatani, Tatsunori; Hayashi, Kei; Morikawa, Momoko; Ozawa, Makoto; Kojima, Isshu; Okajima, Misuzu; Takano, Ai; Shimoda, Hiroshi; Maeda, Ken; Matsuu, Aya; Yoshida, Ayako (Parasitology international, 2020)
The sika deer (Cervus nippon) is one of the most common species of wildlife in Japan. This study aimed to reveal the prevalence of tick-borne protozoan parasites in wild sika deer living in western Japan. We used nested polymerase chain reaction (PCR) to detect the 18S rRNA gene of tick-borne apicomplexan parasites (Babesia, Theileria, and Hepatozoon spp.) from 276 blood and liver samples from sika deer captured in the Yamaguchi, Oita, Kagoshima, Okayama, Ehime, Kochi, and Tokushima Prefectures. In total, 259 samples (259/276; 93.8%) tested positive in the nested PCR screening. Gene sequencing revealed that 99.6% (258/259) of positive samples contained Theileria sp. (sika 1), while Theileria sp. (sika 2), another Theileria species, was detected in only 3 samples. We also found that one sample from a sika deer captured in Kagoshima contained the gene of an unidentified Babesia sp. related to Babesia sp. Kh-Hj42, which was previously collected from tick in western Siberia. In conclusion, we found a high prevalence of piroplasms in sika deer from western Japan, and DNA analysis revealed that Theileria sp. (sika 1) had the highest infection rate.